(untitled) (African Journal of Biomedical Research, 2023)
Drug abuse, a patterned use of a drug in which the user consumes the substance in amounts or with methods which are harmful to themselves or others, is a form of substance-related disorder causing health and social problems, violence, suicides, physical dependence or psychological addiction. As drug abuse has been a cause of physiological or biochemical distortion, this work was primarily set to assess Oxidative genotoxicity and neuronal damage in confirmed and suspected substance abusers. This study included 71 subjects -21 were subjects that exhibited behaviors of drug users, tested and confirmed positive for illicit drugs, 30 were subjects that had stopped using drugs but still exhibited the behaviors of drug users, tested and confirmed negative for illicit drug. The remaining 20 subjects that did not have history of drug abuse served as control. Both 8-Hydroxy-2’-deoxyguanosine (8-OHdG) and creatinine were estimated in urine of all subjects. and 8-OHdG was expressed per mg creatinine. The parameters were compared in all groups and gender. Student t-test was used in comparing means, correlation was also done at p≤ 0.05. Oxidative DNA damage (8-OHdG) and neuronal damage were significantly higher in both group 1 (behavioral positive-drug positive subjects) and group 2 (behavioral positive-drug negative subjects) compared to controls and also when group 1 was compared to group 2. DNA and neuronal damage sequel to drug abuse could be as a result of the biochemical, physiological or pathologic conditions characteristic of drug abusers. This finding may help in designing better management of substance abuse.